Jumlah Batang dan Daun Rumput Raja (Pennisetum Purpureophoides) karena Pengaruh Dosis Pupuk Kompos yang Diperkaya Azolla microphylla - Syarifudin, Ahmad; Hendarto, Eko; Bahrun, Bahrun (ANGON: Journal of Animal Science and Technology, 2021)
Background. The purpose of this research was to examine the effect of compost enriched by Azolla microphylla and determine the optimal fertilizer dosage for the number of stems and leaves of king grass (Pennisetum Purpureophoides) in the third defoliation growth. Materials and methods. The research materials used the third defoliation king grass, compost from cow dung, and Azolla microphylla. The research method was experimental with completely randomized design (CRD) factorial patterns used in the study with the first factor, namely the dose of compost (K) with 3 doses, namely 10, 20, 30 ton / ha / defoliation and the second factor, namely the enrichment of Azolla microphylla (A ) with 3 doses, namely 10, 20, 30% of the dose of compost. There were 9 combination treatments which were repeated 3 times. King grass was planted on treatment plots with a spacing of 80 cm x 40 cm, and a distance between treatment plots of one meter. The research parameters measured were the number of stems and leaves of king grass. Data were analyzed using analysis of variance and followed by orthogonal polynomial test. Results. The results of the analysis of variance showed that the dose of compost had a significant effect (P <0.05) on the number of stems and leaves of king grass. Azolla microphylla dosing had a very significant effect (P <0.01) on the number of stems and leaves of king grass. The results of the analysis show that there is a single effect of each factor and there is no interaction. Conclusion. The results showed that the best treatment combination dose was K3A3, namely compost 30 ton / ha / defoliation, and 30% enrichment of Azolla microphylla.